Curriculum Development Design Based on Character Education to Form Teamwork in Elementary School Students - Sedya Santosa; Syarifah Risma Aulia (Jurnal Ilmiah Sekolah Dasar, 2025)
The main problem in this study is the increasing need for character education in the era of globalization and digitalization. On the other hand, the integration of moral values into the elementary school curriculum is still not going well. This study aims to examine the design of character education-based curriculum development in forming teamwork in school students. This type of research is qualitative with a field research approach. The subjects of the study consisted of principals, teachers, and students in one school. Data collection methods were carried out through observation, interviews, and documentation. Data analysis used data condensation techniques, data presentation, and drawing conclusions to identify patterns and themes that were in accordance with the focus of the study. The results showed that the implementation of a character education-based curriculum had a positive impact on students' teamwork skills. values such as discipline, responsibility, and four are seen in social interactions and activities at school. The conclusion of this study is that the design of a character education-based curriculum not only improves students' academic achievement but also strengthens the formation of moral values.